Ascorbic acid in cosmetic formulations: Stability, in vitro release, and permeation using a rapid, inexpensive, and simple method - Spagnol, Caroline Magnani [UNESP]; Ferreira, Guilherme Alves [UNESP]; Chiari-Andreo, Bruna Galdorfini [UNESP]; Borges Isaac, Vera Lucia [UNESP]; Correa, Marcos Antonio [UNESP]; Nunes Salgado, Herida Regina [UNESP] (Taylor & Francis Inc, 2017)
Ascorbic acid (AA) is involved in important metabolic processes in the human body. However, its chemical instability requires the assessment of products containing AA. The aim of this study was to develop systems that improve AA stability and to evaluate its release profile, permeation, and skin retention in vitro. For this purpose, we prepared binary systems consisting of propylene glycol and water, microemulsions, liquid crystalline systems, and an emulsion. The AA content in these systems was evaluated over time by measuring the inhibition of 1,1-diphenyl-2-picrylhydrazyl (DPPH). Our results demonstrated that the binary systems and molecular aggregates were less stable and effective than the emulsion. Thus, in vitro AA release, skin permeation, and retention were evaluated using the emulsion. Our results indicate that AA exhibits low release and permeation levels and a high retention rate in the skin, characteristics desirable in cosmetic products. [GRAPHICS] .
Keywords: Ascorbic acid; skin permeation and retention; stability; vitamin C